Crime, Justice, and Social Order: Essays in Honour of A. E. Bottoms - Liebling, Alison (Clarendon Studies in Criminology Ser., 2022)
To honour the extraordinary contribution of Professor Anthony Bottoms to criminology and criminal justice, leading criminologists and penal scholars have been asked to contribute original essays on the wide range of areas in which he has written. The book also contains a major essay by Anthony Bottoms, on Criminology and 'positive morality'.